Converting Stereo Microphone Signals Directly to MPEG-Surround - Tournery, Christophe; Faller, Christof; Küch, Fabian; Herre, Jürgen (128th Audio Engineering Society Convention 2010, 2010)
We have previously proposed a way to use stereo microphones with spatial audio coding to record and code surround sound. In this paper we are describing further considerations and improvements needed to convert stereo microphone signals directly to MPEG Surround, i.e. downmix signal plus bitstream. It is described in detail how to obtain from the microphone channels the information needed for computing MPEG Surround spatial parameters and how to process the microphone signals to transform them to an MPEG Surround compatible downmix.
Vorträge und Veröffentlichungen auf Konferenzen_Mehrkanalige Codierung von Audiosignalen